Driving cycle development methods: case study in Malaysia - Nurru Anida Ibrahim; Siti Norbakyah Jabar; Arunkumar Subramaniam; Wan Nural Jawahir Wan Yussof; Salisa Abdul Rahman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Over the years, many models have been created to estimate pollution inventories and fuel usage. These models can be divided into two types: travel-based and fuel-based. One of the most used travel-based models for estimating emission inventories is driving cycles. It can be used for a variety of different things, such as establishing pollution regulations, traffic control, and calculating journey time. For these goals, researchers have previously attempted to use easily available, well-established driving cycles. In many ways, however, the local environment differs greatly from that of the driving cycle’s genesis. As a result, these cycles’ applications have failed to provide high-quality results. This research aims to analyse the various approaches utilised for driving cycle construction in various locations of Malaysia under varied operational situations.